Giant colonic leiomyoma mimicked as a gynecological tumor: a case report - Kutty, Sathiamma Puthuvilayil; Kandy, Afsara Karuvan; Jacob, Sheela; I., Prassetha; Mathew, Tilka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Colonic leiomyomas are rare benign smooth muscle tumors that account for a small percentage of gastrointestinal tumors. These tumors often pose diagnostic challenges due to their similarity to other smooth muscle tumors, such as gastrointestinal stromal tumours (GIST), and their potential to mimic gynaecological or adnexal masses. In this report, we present the case of a 43-year-old female who presented with vague abdominal symptoms and was found to have a large extraluminal mass in the colon. Initial radiologic evaluations suggested a gynaecological or adnexal origin, particularly mimicking a uterine leiomyoma or ovarian tumour. However, immunohistochemistry (IHC) confirmed the diagnosis of colonic leiomyoma, which was successfully managed through surgical resection. This case underscores the importance of considering colonic leiomyomas in the differential diagnosis of large abdominopelvic masses, particularly when imaging suggests other origins. It also highlights the essential role of IHC in distinguishing colonic leiomyomas from GIST and other similar tumours to ensure accurate diagnosis and appropriate treatment.